The Effect of Digital Flipchart Training on Special School Teachers’ Knowledge about Reproductive Health Education for Adolescents with Disabilities - Ismi Nur Khasanah; Rahma Trisnaningsih; Mizan Prihastuti; Lutfi Annarahayu; Saumi Fijriyah; Siti Mahmudah (Indonesian Journal of Nursing and Health Sciences, 2026)
Adolescents with disabilities often encounter barriers in accessing reproductive health information. Teachers in special education settings play a crucial role in delivering such education; however, many lack adequate knowledge and appropriate teaching media. This study aimed to determine the effect of digital flipchart training on special school teachers knowledge about reproductive health education for adolescents with disabilities. A pre-experimental study with a one-group pre-test–post-test design was conducted among 160 teachers from special schools (SLB) in Bantul regency. A pre-experimental study with a one-group pre-test–post-test design was conducted among 160 teachers from special schools (SLB) in Bantul Regency. The intervention consisted of a one-day training session using a digital flipchart containing interactive reproductive health materials adapted for students with disabilities. Teachers’ knowledge was measured using a 20-item questionnaire that had demonstrated good content validity through expert review and high internal consistency (Cronbach’s α = 0.85) before and after the training. Data were analyzed using the paired sample t-test. Results: The mean pre-test score was 5.40 ± 0.59, which increased to 5.63 ± 0.63 in the post-test (t = 2.04, p = 0.048). These findings indicate that the LEBAD-based training effectively enhanced participants’ understanding of reproductive health education for students with disabilities. Digital flipchart training effectively enhances teachers’ knowledge and supports inclusive reproductive health education in special schools.